Eco-Sufism of Kajang Tribe in the Tradition of "Pasang Rikajang" Indigenous Community of Sulawesi, Indonesia - Haq, Syamsul; Lubis, Sopian; Raqieb, Achmad; Agustin, Suci (Mimbar Agama Budaya, 2024)
This research aims to assess the compatibility between the legacy of Pasang ri Kajang and the Sufistic ideal. The research methodology used a literature review approach, utilizing various scientific publications, books, and articles. The research used sample data from the Kajang community located in Bulukumba Regency, South Sulawesi. The findings of this study indicate that the Pasang tradition shows compatibility with the value of Sufism values sourced from God (Turie A'rana), which has been passed down from generation to generation by the first Ammatoa generation (Too Riolota). The principle of the Pasang tradition is harmony with the relationship between humans and God, as well as the relationship between humans and their natural environment. As well as upholding sufficiency and simplicity of lifestyle that aims to give more respect to the forest, as well as environmental ecosystem management. This conformity is in line with Sufistic principles